Studi Biologi Pleisispa reichi Chap. (Coleoptera: Crhysomelidae) di Laboratorium - Darma Bakti; Rosmayati Rosmayati; Sufryiadi Sufryiadi (Jurnal Agrista, 2009)
Biological Study of Pleisispa reichi Chap. (Coleoptera: Crhysomelidae) in LaboratoryABSTRACT. Pleisispa reichi is a mein pest of coconut in Indonesia. This beetle attacked the young leaves. The objective of this research id to know the biological aspect of this beetle on coconut leaves. This studies were conducted in Laboratory of plant pest and disease, Faculty of Agriculture, North Sumatera level. The result showed that female produced 43.40±9.86 eggs with hatching 80.77±6.95%. Larvae had 3 instars with duration 22.80±0.79 days. The age of pupae 5.30±0.71 days. While the age of female and male, 70.90±4.55 and 73.90±4.55 days, respectively. Copulation occurred when imagoes age 13-14 days. The length and wide size of eggs were 5.90±0.56 and 1.95±0.20 mm. The length larvae of instar 1, 2, and 3 were 4.05±0.37, 6.00±0.53, and 9.05±0.55 mm. While the width were 0.95±0.16, 1.35±0.24, and 1.85±0.24 mm. The measure of length and width of pupa were 8.75±0.49 and 1.80±0.26 mm. While the length and width size of male was 8.35±0.58 mm and 1.90±0.21 mm and the female was 9.75±0.54 mm and 2.20±0.26 mm. In life table showed that the net of reproduction rate (Ro) = 11.02. While the intrincic rate of reproduction (r) was 0.070 and Tc was 34.30. It means that the beetle had survival rate was 34.30%.